Physical Fitness Level of Athletes of SSB Gempuri Rengat - Hamdani, Muhammad Fadhli; Apriani, Leni (Indonesian Journal of Sport Management, 2025)
The purpose of this study was to determine the level of physical fitness of SSB Gempuri Rengat athletes. This type of research is Descriptive research, while the data collection techniques used are tests and measurements. The population of this study were all SSB Gempuri Rengat athletes totaling 16 people. Then the sample was limited by male athletes totaling 16 people. The research instrument used was the TKJI test. Based on the results of the study, the conclusions obtained in this study are: the level of physical fitness of SSB Gempuri Rengat athletes is included in the score range of 14-17 or with a percentage of 43.75% in the Moderate category.